Lincoln's Gettysburg Address : Given November 19, 1863 on the battlefield near Gettysburg, Pennsylvania, USA - Lincoln, Abraham, 1809-1865 (Salt Lake City, UT : Project Gutenberg, 1973)
"Lincoln's Gettysburg Address" by Abraham Lincoln is a speech delivered on November 19, 1863, at the dedication of Soldiers' National Cemetery in Gettysburg, Pennsylvania. Following the Civil War's deadliest battle, Lincoln spoke for less than two minutes before 15,000 people, delivering only 271 words. He invoked the Declaration of Independence and honored those who died defending the nation's founding principles, closing with his famous vision of "government of the people, by the people, for the people." (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Gettysburg_Address
Release date is 1973-11-01
Keywords: Consecration of cemeteries -- Pennsylvania -- Gettysburg; Soldiers' National Cemetery (Gettysburg, Pa.); Lincoln, Abraham, 1809-1865. Gettysburg address